A. R. Luria and the Twin Method in Modern Medical Genetics - Tskhovrebova, L (KnE Life Sciences, 2018)
The twin method is one of the classical methods of medical genetics which aids in defining the role of factors of heredity and environment in traits of norm and pathology, to study development of multifactorial diseases and development of genetics of intellectual activity. From the genetic point of view twins may be either monozygotic or dizygotic. The field of intellectual activity, in particular learning ability, attention and memory is most difficult and inaccessible for the genetic analyses of twins. The very beginning of research of twins’ intellectual activity was laid by A.R. Luria in years 1920-1930 and the features of development of twins of various age were revealed. Using tasks that required mental capacities of different levels: immediate memory vs cultural forms of mediated memory, Luria’s group compared results of monozygotic and dizygotic twins of different ages (5-7 and 11-13). It has been shown that monozygotic twins are much more similar between themselves concerning mental capacities, natural forms of memory than dizygotic twins. In the older group it was the same difference in natural forma, but much less difference between monozygotic and dizygotic tweens in culturally determined forms of memory. Much more similarity was observed between monozygotic twins who grew separately, than between dizygotic, being raised in the identical social environment. During these researches a number of assumptions have been stated about « the influence of heredity on intellectual activity which will be revealed in the solution of tasks which don’t demand special knowledge». Prospects of modern researches are in comparison of concordance mono-and dizygotic twins, confirming A. R. Luria’s assumption of interrelation of natural memory and intellectual endowments of twins with their genotype. Medical genetics confirms that the extent of development of various intellectual traits of monozygotic and dizygotic twins is caused first of all by influence of the environment – training and experience which is revealed is increased in increased variability of most intellectual characteristics at the age of 14–16 years. Keywords: A.R.Luria, twin method, medical genetics, epigenetic changes.